2012
DOI: 10.2147/dmso.s27665
|View full text |Cite|
|
Sign up to set email alerts
|

Randomized, double-blind, placebo-controlled, linear dose, crossover study to evaluate the efficacy and safety of a green coffee bean extract in overweight subjects

Abstract: BackgroundAdult weight gain and obesity have become worldwide problems. Issues of cost and potential side effects of prescription weight loss drugs have led overweight and obese adults to try nutraceuticals that may aid weight loss. One promising nutraceutical is green coffee extract, which contains high concentrations of chlorogenic acids that are known to have health benefits and to influence glucose and fat metabolism. A 22-week crossover study was conducted to examine the efficacy and safety of a commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 23 publications
(28 reference statements)
0
39
0
1
Order By: Relevance
“…NAFLD patients in the placebo group (n = 22) assigned to receive the same amount of placebo for the same time. Safety of the dose and duration of the study has been verified in previous studies (23,24). The capsules were given to the patients at the time of randomization and at the 4 th -week followup visit.…”
Section: Interventionmentioning
confidence: 88%
“…NAFLD patients in the placebo group (n = 22) assigned to receive the same amount of placebo for the same time. Safety of the dose and duration of the study has been verified in previous studies (23,24). The capsules were given to the patients at the time of randomization and at the 4 th -week followup visit.…”
Section: Interventionmentioning
confidence: 88%
“…And so forth, relate the change in HbA1c concentration to an increase in polyphenols intake. In this case, only 7 (Balzer et al, 2008;Curtis et al, 2012;Fenercioglu et al, 2010;Kudolo et al, 2005;Pan et al, 2007;Toolsee et al, 2013;Vinson et al, 2012) of the trial included in the meta-analysis included polyphenol metabolites analysis or antioxidant capacity assay.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study showed significant reductions in body weight, body mass index, and percent body fat, but with no significant alterations in dietary intakes over the course of the study. Finally, this study suggested that commercial green coffee extract product GCA ™ might be an effective nutraceuticals in reducing weight in pre-obese adults, and might be an inexpensive means of preventing obesity in overweight adults [28]. The results of a systematic review and metaanalysis of randomized clinical trials revealed a significant difference in body weight in GCE compared with placebo (mean difference: -2.47 kg; 95% CI: -4.23, -0.72).…”
Section: Resultsmentioning
confidence: 77%
“…Several human clinical trials have also conducted to examine the efficacy and safety of commercial GCE at reducing weight and body mass in overweight and obese adults [24][25][26][27][28]. The results from a clinical study performed on 30 overweight people showed consumption of instant coffee enriched with cholorogenic acid for 12-week induced a significant reduction in body mass index and body fat, compared with the control [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation